The importance of local long-duration STEM mentorship as a global mechanism for increasing diversity at all levels of education - Gallagher Dunn, Sarah Louise; Haviland, Heidi Fuqua; Gallagher, Dennis Lee (Frontiers in Astronomy and Space Sciences, 2023)
We begin with a brief review of the progress being made by the professional space physics community to increase diversity and inclusion. These efforts have been primarily centered on overcoming barriers that have inhibited existing underrepresented minority space physics professionals from being successful at all levels of academic, mission, and administrative achievement. While we find these remediations to be essential, we must recognize that our ability to achieve a diverse professional workforce representative of the US population depends on achieving a diverse population of researchers entering the field. That means the greatest gains can only be achieved by actions that reach into the educational system. We identify and discuss possible issues within the traditional formal education and developmental environment of young inquiring minds, including gaps in resources, the pressure to bring in income during secondary school and graduate school matriculation, and the cultural biases against research careers. We highlight the importance of local mentorship and age-appropriate research-like activities within all levels of education, including Kindergarten through bachelor’s and advanced degree programs, as a means of overcoming barriers to becoming a respected contributing member of the space physics research community. We note these issues extend beyond space physics into all STEM fields. These activities can provide road maps into research careers, practice age-appropriate skills, and provide an avenue for current researchers to become mentors. Specifically, we advocate the development of a formal program of professional chapters for colleges and age-appropriate research-oriented programs for K-12 schools and encourage strong collaborative affiliations with other professional societies. At the core of this is the development and implementation of informed, persistent mentoring.